Notes on the problem of the optimum design of structures - Hemp, W. S. (College of Aeronautics, 1958)
The urgent need for a systematic approach to the problems of the optimum design of structures is stressed and ideal formulations of these problems are considered. Differential equations and a variational principle are derived for the case of plates loaded in their own planes; these can form the basis for approximate solutions, in the form of optimum distributions of plate thickness and the corresponding stress distributions which are required to equilibrate given systems of external loads.